How populists engage religion: mechanisms and evidence from the Philippines. Issue 8 (17th November 2022) - Buckley, David T.; Brooke, Steven; Kleinsteuber, Bryce
ABSTRACT: Despite increasing interest in populism and religion, scholars generally lack a conceptual foundation to distinguish strategies through which populists integrate religion into mobilisation. We use the case of Rodrigo R. Duterte's Philippines to derive a four-part typology of such interactions grounded in distinct dimensions of populism. This typology distinguishes causal mechanisms and clarifies how, even within a single country, populists may opportunistically blend several religious strategies to suit their personalistic political ends. Populists may draw on religious norms and identity to buttress boundaries between in-groups and out-groups, credibly signal their outsider status by challenging religious hierarchies, leverage personalistic linkages to religious elites, and deploy a populist style with religious affinities. We trace how such strategies may cement religious support, and, at times, motivate religious resistance to populist rule. A systematic subnational assessment correlating religious demographics and Duterte's voteshare in his 2016 election across over 40, 000 Philippine subdistricts evaluates empirical implications of each pathway using relevant religious communities.